PERAN SUBJECTIVE WELL-BEING, KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL DALAM MEMPREDIKSI KINERJA KARYAWAN - Mutiarini Mubyl; Giri Dwinanda (Jurnal Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to look at the role of subjective well-being, transformational leadership, and organizational commitment to employee performance. This study uses a quantitative non-experimental method with a total sample of 89 marketing employees of KSP MU. The results of this study prove that subjective well-being (tcount = 2.796> 1.987; 0.006 <0.050), transformational leadership (tcount = 3.709> 1.987; 0.000 <0.050), and organizational commitment (tcount = 2.290> 1.987; 0.025 <0.050) significant and positive to employee performance separately. The three variabels also have a significant and positive effect on employee performance simultaneously (Fcount= 58,228> 2.71; 0,000 <0.050). The value of contribution / role of the three independent variabels on employee performance seen from the value of the determination coefficient (R2) that is equal to 67.3%, while the remaining 32.7% employee performance is influenced by other variabels that not included in this study. The independent variabel that most plays a role in predicting employee performance is transformational leadership which is equal to 0.379, compared to subjective well-being (0.339) and organizational commitment (0.178). So that this answers all existing hypotheses, H0 is rejected and H1 - H6 are accepted.